PERGESERAN MAKNA PADA ADJEKTIVA「スマート」 - wanda, salma; Frida Philiyanti (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2021)
The purpose of this research is to understand the semantic change of the word "smart" in Japanese. "Smart" is originally an English word, meaning Clever, Fashionable, and Smart. However, in Japanese, "smart" has four meanings: "clever," "fashionable," "high-tech," and "slim." The question in this study is how the change in the meaning of “Sumaato” occurs, grammatically based on context and structure. This research was conducted by the method of literature perspective, with reference to books, journals, and online articles. The data source is taken from Twitter by searching for the keyword "Sumaato" in the search column, then translate to Indonesia Language, and compared with equivalent word based on KBBI. As a result of this research, from the context, from the four meanings of "smart," the only semantic change is "slim" which is categorized as semantic shift. And from the grammatical structure, you can also add the suffix "Sa" after the word "smart". Keywords: semantic change, semantic shift, sumaato